2015
DOI: 10.1103/physrevlett.114.115503
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Induced Rupture of Strained Si─O Bonds in Amorphous Silicon Dioxide

Abstract: Using ab initio modeling we demonstrate that H atoms can break strained Si-O bonds in continuous amorphous silicon dioxide (a-SiO2) networks, resulting in a new defect consisting of a 3-coordinated Si atom with an unpaired electron facing a hydroxyl group, adding to the density of dangling bond defects, such as E centers. The energy barriers to form this defect from interstitial H atoms range between 0.5 and 1.3 eV. This discovery of unexpected reactivity of atomic hydrogen may have significant implications fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 59 publications
(61 reference statements)
2
45
0
1
Order By: Relevance
“…We therefore speculate that the measured activation/deactivation times are either limited by the time taken to release hydrogen for instance at the gate interface or by the barrier at the defect site preventing the reaction. Once the defect is deactivated by a hydrogen reaction, another H reaching the site would re-activate that defect again [30], see defect I2. Alternatively, H 2 and H could attack a strained Si-O bond to form an active defect/passivated precursor (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore speculate that the measured activation/deactivation times are either limited by the time taken to release hydrogen for instance at the gate interface or by the barrier at the defect site preventing the reaction. Once the defect is deactivated by a hydrogen reaction, another H reaching the site would re-activate that defect again [30], see defect I2. Alternatively, H 2 and H could attack a strained Si-O bond to form an active defect/passivated precursor (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in our previous DFT studies [12,23] where we compared theoretical predictions to TDDS experiments, we have identified hydrogen-related E -centers as interesting defect candidates. One of these candidates, the hydroxyl E -center [30], is shown in Fig. 14 (right) together with a few possible ways it may interact with H and H 2 (left).…”
Section: Discussionmentioning
confidence: 99%
“…For example, atomic hydrogen does not react with terraces at the MgO (001) surface, but donates electrons to three-coordinated Mg sites at corners and kinks at that surface, creating new [Mg + − O-H]-type centers [35,36]. The recent study of amorphous silica has concluded that, unlike in α quartz, atomic H can break some strained Si-O bonds and form a new thermodynamically stable defect, termed hydroxyl E center [37,38]. In this case, the electron is localized on a Si atom and a proton forms an O-H bond nearby.…”
Section: Introductionmentioning
confidence: 99%
“…Namun demikian, dengan penyinaran yang lama, hydrogen justru dipercaya menimbulkan dangling bond baru yang berakibat turunnya kinerja dari sel surya [4]. Karena itu banyak sekali penelitian teoritis dilakukan untuk mencari tahu mekanisme sebenarnya dari efek positif maupun negatif dari Hidrogen karena sampai saat ini mekanisme detail nya belum bisa disepakati oleh para peneliti [5,6]. Hal ini juga tidak terlepas dari pengetahuan bagaimana ikatan-ikatan atomik terbentuk saat terjadi hidrogenisasi silikon amorf.…”
Section: Pendahuluanunclassified